Mulheres por mulheres: a representação do amor, do corpo e da sexualidade nas identidades femininas da coleção amores extremos - Ed. Record - Bergamasco, Adrielle dos Santos (2016)
The aim of this research, of bibliographic and qualitative character, is to analyze the love mode of representation, the body and sexuality in the trajectory of female characters that make up the series Amores extremos, composed of seven novels written by Brazilian writers, published by publisher Record, between the years 2001 to 2003. It is more specifically to investigate what are the choices that contemporary writers make when building their characters, include stigmatized minorities or remains the representations that traditionally populate the novels in overall, often reduplicate the standards of patriarchal-dominant society. The research is justified by continuing other studies previously dealing with women's representation in the literature (for female authors) and to contribute to literary studies on this theme. Based on the literary analysis, it was based on feminist literary criticism and related theories, such as Pierre Bourdieu, Alain Touraine, Judith Butler, Regina Dalcastagnè, Elódia Xavier, among others. As a result, it can be said that the literature of contemporary female authors, in fact represent the female identity (s), differently from the one (s) traditionally represented, by proposing a plurality of new identity forms and give a different look, based on feminist thought, to gender issues and the relations between them. It also includes spontaneously female sexuality, being more intimate, expressive representations and closer to those experienced in extraliterary reality, by giving voice to the women themselves to live their sexuality. In this sense, women represented by this literature are free, independent, libertarian and actresses of their own lives, acting with awareness and responsibility for their actions, thus demonstrating the relevance of this literature for a more coherent representation of women in the way of being of women in contemporary society